2008
DOI: 10.1007/s11013-008-9122-2
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Placebo Response from a Broad Anthropological Perspective

Abstract: This paper considers how the full range of human experience may catalyze a placebo response. The placebo effect has been characterized as something to control in clinical research, something to cultivate in clinical practice, and something present in all healing encounters. We examine domains in which the term 'placebo' is used in discourse: clinical research, clinical practice, media representations of treatment efficacy, and lay interpretations of placebo-an under-researched topic. We briefly review major th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 150 publications
2
92
0
3
Order By: Relevance
“…Essential components of the total context are the doctor's attitude, especially his or her communication skills, the doctorpatient relationship, the way the doctor applies therapeutic procedures or rituals, and, ultimately, the doctor's ability to create trust. [3][4][5][6] …”
Section: Symptoms and The Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…Essential components of the total context are the doctor's attitude, especially his or her communication skills, the doctorpatient relationship, the way the doctor applies therapeutic procedures or rituals, and, ultimately, the doctor's ability to create trust. [3][4][5][6] …”
Section: Symptoms and The Brainmentioning
confidence: 99%
“…Over the past 20 years, much empirical research has shown impressive symptommodulating effects, not only from the placebo pill, but also from the context surrounding the encounter between patient and therapist (including therapists practising complementary and alternative procedures, for example, acupuncture). 4,5,7 In addition, new types of scanning technology have allowed us to study the biological processes in the brain intensively during the past 10 years, and these processes have been demonstrated to be strongly influenced by a variety of contextual factors. The biological processes and the variations in the context-mediated effects in the brain have now been scientifically proven.…”
Section: Research In Symptom Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeśli pacjent nie chce rozmawiać w trakcie masażu, terapeuta nie powinien inicjować rozmowy. Zawsze warto pamiętać o tym, że najgłębsze oddziaływanie masażu relaksacyjnego ma miejsce wówczas, gdy pacjent zasypia w trakcie zabiegu [15].…”
Section: Warunki Przeprowadzenia Zabiegu Masażu Relaksacyjnegounclassified
“…If the patient does not want to talk, the therapist should not initiate the conversation. It is always worth remembering that best results of relaxing massage are achieved when the patient falls asleep during the procedure [15]. 3.…”
Section: The Conditions Of Performing Relaxing Massagementioning
confidence: 99%